-mercaptoethanol can reverse the inhibition of some glycolytic enzyme activities of Streptococcus mutans UA159 by benzimidazoles - Mai Phuong, Nguyen Thi; Marquis, Robert E. (Academia Journal of Biology, 2014)
Benzimidazoles, such as omeprazole (OM) or lansoprazole (LAN), are widely used as proton-pump inhibitors to control stomach hyperacidity and have been found also to have antimicrobial actions against Helicobacter pylori and oral streptococci. Our study indicated that OM and LAN affected the glycolysis of oral bacteria by inhibiting the activity of some glycolytic enzymes of Streptococcus mutans UA159 including aldolase, glyceraldehyde phosphate dehydrogenase and lactate dehydrogenase. Remaining activity of these enzymes after had been treated with the agents were ca. 30%, 50% and 60%, respectively. However, pyruvate kinase was not inhibited by OM and LAN. Benzimidazoles are effective in the protonated form at acid pH values and cause inhibition of enzymes associated with the formation of drug-target disulphide bonds. We found that reducing agents including b-mercaptoethanol and glutathione reversed the inhibition of glycolytic enzyme activities by benzimidazoles. The reason for that possibly is the reducing agents neutralized benzimidazoles, avoiding the formation of S-S bonds between the protonated forms of drugs and target enzymes. Thus, glycolytic pathway is a potential target for the use of benzimidazoles against oral streptococci and their antimicrobial activity could be eliminated by the reducing agents.